Biological Evaluation of l‐Tyrosine Labelled with fac‐[99mTc(CO)3]+ at a para‐OH‐Coupled 2, 3‐Diaminopropionic Acid Based Chelator. Issue 12 (15th February 2017) - Felber, Michael; Bauwens, Matthias; Imstepf, Sebastian; Fox, Thomas; Mottaghy, Felix M.; Alberto, Roger
Abstract : Radiolabeled amino acids as metabolic tracers are increasingly important for imaging and therapy applications. There are only a few reports on 99m Tc‐labeled amino acids that have been evaluated in vivo. In this work we coupled a small and highly potent chelator for the fac ‐[ 99m Tc(CO)3 ] + core to l ‐tyrosine through a poly(ethylene glycol) linker and investigated the in vivo biodistribution of the 99m Tc‐labeled l ‐tyrosine derivative. In vivo evaluation and biodistribution in mice bearing C6‐tumor xenografts revealed little tumor and pancreas uptake. The microSPECT images showed rapid clearance from the blood pool. Fast uptake into the gallbladder and an extended residence time makes this labeled tyrosine suitable for gallbladder imaging and associated dysfunctions. Abstract : Radiolabeled amino acids are important imaging agents for rapidly proliferating cells. Tyrosine has been coupled to a tripod ligand and labeled with 99m Tc in a two‐step or one‐pot reaction. Accumulation in tumor xenografts was small, but fast uptake into the gallbladder and retention over an extended period suggest that this compound is suitable for gallbladder imaging and related dysfunctions.